Yield Predictive Worth of Pre-Flowering and Post-Flowering Indicators of Nitrogen Economy in High Yielding Winter Wheat - Witold Szczepaniak; Witold Grzebisz; Jarosław Potarzycki (Agronomy, 2022)
Indicators of nitrogen economy in winter wheat during vegetative development are a reliable tool for yield prognosis. This hypothesis was verified in a field experiment, carried out in the 2013/2014, 2014/2015, and 2015/2016 seasons. The field experiment, in a two-factor split-plot design, included the following systems of wheat protection (CFP): (i) N + micronutrients, (ii) N + fungicides, (iii) N + micronutrients + fungicides; and N rates: 0, 40, 80, 120, 160, 200, 240 kg N ha−1. The content and accumulation of N in wheat at the beginning of stem elongation and at heading were used for grain density and yield prediction. In the grain-filling phase, the stem N acted as a buffer, stabilizing yield at a high level. The condition for such action was the stem N equilibrium with the ear N at flowering. The N depletion from the leaves during the grain-filling period significantly depended on the grain density. The post-flowering uptake of N by wheat was affected by the grain density, which was affected by the N reserves in the stem. Yield forecast based on pre-flowering indices of nitrogen economy in cereals affects both agronomic decisions aimed at correcting the nutritional status of plants, and farm economics.